PENAMBAHAN EKSTRAK Sargassum sp. HASIL EKSTRAKSI ENZIMATIK PADA PAKAN TERHADAP PERFORMA PERTUMBUHAN UDANG VANAME (Litopenaeus vannamei) - Tri Mulyadi; Sarjito Sarjito; Diana Rachmawati (Departemen Akuakultur FPIK UNDIP, 2020)
Intensification of white shrimp (L. vannamei) cultivation causes accumulation of waste aquaculture in the water and environmental stress which causes pathogenic organisms to develop and attack aquaculture organisms, so that mass deaths occur. Various efforts have been made to overcome this through feed production by adding ingredient that can enhance the body's immune system, but also function as growth promoters. The material that has both functions is seaweed Sargassum sp. The aims of this study was to determine the addition effect of sargassum extract from enzymatic extraction on feed to the specific growth rate/SGR and feed convertion ratio/FCR of white shrimp (L. vannamei). These study was conducted by experimental method used a completely randomized design (CRD) with 3 treatments and 2 repetitions. The treatment was namely A (feed with the addition of sargassum extract 0 g/kg feed), B (feed with the addition of enzymatically protease sargassum extract 2 g/kg feed) and C (feed with the addition of enzymatically carbohydrase sargassum extract 2 g/kg feed). The results showed that the feed with the addition of sargassum extract from enzymatic extraction had a significant effect (P<0,05) on specific growth rate (SGR) and feed conversion ratio (FCR). Water quality of media is in the proper range for shrimp farming.